Endoscopic vacuum therapy for esophageal perforations and leakages - Oliver Möschler; Christoph Nies; Michael K. Mueller (Endoscopy International Open, 2015)
Background and study aims: Injuries to the esophageal wall, such as perforations and anastomotic leaks, are serious complications of surgical and endoscopic interventions. Since 2006, a new treatment has been introduced, in the form of endoscopically placed vacuum sponge therapy. Patients and methods: Between April 2012 and October 2014, 10 patients (5 men and 5 women) aged 57 to 94 years were treated at our institution using endoscopic vacuum therapy (EVT) in the upper gastrointestinal tract. Results: The defect in the esophageal wall was successfully closed in seven of the 10 patients (70 %). No severe complications occurred. Conclusions: EVT is a valuable tool for management of defects in the esophageal wall and should be considered as a treatment option for patients with this condition.